Fungal metabolic profile dataset was not influenced by long-term in vitro preservation of strains - Veselská, Tereza; Kolařík, Miroslav (Data in brief, 2019)
Comparative ecophysiology is highly valuable approach to reveal adaptive traits linked with specific ecological niches. Although long-term in vitro preserved fungal isolates are often used for analyses, only sparse data is available about the effect of such handling on fungal physiology. The purpose of our data is to show the effect of long-term in vitro preservation of fungal strains on their metabolic profiles. This data is related to research paper "Adaptive traits of bark and ambrosia beetle-associated fungi" (Veselská et al., 2019). Biolog MicroPlates™ for Filamentous fungi were used to compare metabolic profiles between freshly isolated and long-term in vitro preserved strains of two Geosmithia species. Additionally, carbon utilization profiles of 35 Geosmithia species were assessed, including plant pathogen G. morbida and three ambrosia species. Data also shows differences in carbon utilization profiles among diverse ecology types presented in the genus Geosmithia.
Keywords: Metabolic profile; Fungal physiology; Biolog microarray; In vitro preservation; Fungi; Comparative ecophysiology